Tuberculosis treatment outcomes among prisoners and general population in Zomba, Malawi - Victor Singano; Esther Kip; Wilson Ching'ani; Lawrence Chiwaula (BMC, 2020)
Abstract Background TB remains a major global health problem. It is particularly prevalent in prisons in sub-Saharan Africa due to overcrowding, malnutrition, high HIV prevalence and insufficient medical services. Prisoners have experienced worse TB treatment outcomes than the general population. The researchers investigated the TB treatment outcomes and predictors of unsuccessful treatment outcomesamong prisoners and the general population in Zomba, Malawi. Methods We retrospectively reviewed TB registers of prisoners and the general population diagnosed with TB from January 2011 to December 2016 at Zomba Maximum Central Prison and Zomba Central Hospital, Malawi. The study used routinely collected data extracted from national, standardized TB treatment monitoring tools. Successful treatment outcome was classified as the total for cured and completed treatment while unsuccessful treatment outcome was classified as the total of deaths and treatment failures. We used descriptive statistics to compare the demographics and TB treatment parameters among prisoners and non - prisoners and computed multivariate analysis to predict the independent factors of unsuccessful treatment outcomes. Results Of 1652 registered cases, 27% were prisoners (all males) and 72% were non-prisoners (58% males). The median age was 35 years (IQR: 29-42); 76% were Pulmonary TB cases (78% among prisoners vs 75% among general population); 83% were new TB cases (77% among prisoners vs 86% among general population); and 65% were HIV positive (50% among prisoners vs 71% among general population). Regarding treatment outcome, 1472 (89%) were cured and/or completed treatment (93% among prisoners vs 88% among general population), 2(0.2%) were treatment failures, 122 (8%) died (5% among prisoners vs 8% among general population) and 55 (3%) were not evaluated (1% among prisoners vs 4% among general population). Unsuccessful TB treatment outcomes were associated with age greater than 35 years (aOR = 0.68: 95% C.I: 0.58-0.80), Extra-Pulmonary TB (aOR = 1.69: 95% C.I: 1.08-2.63) andHIV positive status (aOR = 0.63: 95% C.I: 0.42-0.94). Conclusion Maximum prisons provide a stable population that can be easily monitored throughout the course of TB treatment. Good TB treatment outcomes which are comparable to the general population can be achieved among Malawian prisoners despite the challenging prison conditions.